Para além dos microvídeos no Tiktok: A experiência midiatizada da circulação e do esvaziamento de sentidos sobre a privacidade de dados - Martins , Alessandra Olinda (2024)
The algorithmic practices of digital platforms, especially TikTok, profoundly resignify the concept of privacy in the contemporary context. This paper explores how the culture of the algorithm, the datafication of users, and insertion into a new socio-economic regime (surveillance capitalism; Zuboff, 2020) modulate users' perceptions and interactions with privacy. Based on the theoretical-methodological model of the circuit of culture (Du Gay et al., 1997) to investigate the complex interactions between users, data, and the platform, the study highlights the production and consumption of meanings associated with privacy. In the datasphere (Beiguelman, 2021), privacy is challenged by the omnipresence of the constant flow of data and manipulated by the culture of the algorithm, becoming an element of resistance and reflection. Privacy is thus involved in new dynamics of power and influence, redefining itself amid datafication. Digital platforms and algorithmic practices expand the capacity for communication and interaction and transform symbolic forms of consumption, creating cultural and social capital specific to the digital age. The study highlights the intricate relationship between the TikTok platform's production and consumption of data and users' perception of privacy. Analysis of the privacy policy and published content reveals how the interaction between data collection and surveillance capitalism permeates the user experience by analyzing and re-signifying personal information (their own and that of others). This emerging socio-economic scenario, marked by technological mediation, reconfigures narratives and shapes identity construction in the face of information overload, feeding the polysemy and emptying the concept of privacy.